2010
DOI: 10.1161/circgenetics.109.903898
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Genetic Counseling, DNA Diagnostics, and Cardiologic Family Screening in Left Ventricular Noncompaction Cardiomyopathy

Abstract: Background-Left ventricular (LV) noncompaction (LVNC) is a distinct cardiomyopathy featuring a thickened bilayeredLV wall consisting of a thick endocardial layer with prominent intertrabecular recesses with a thin, compact epicardial layer. Similar to hypertrophic and dilated cardiomyopathy, LVNC is genetically heterogeneous and was recently associated with mutations in sarcomere genes. To contribute to the genetic classification for LVNC, a systematic cardiological family study was performed in a cohort of 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
2
31

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 47 publications
4
150
2
31
Order By: Relevance
“…9,12 This study confirms our previous results demonstrating that pathogenic variants in another sarcomeric protein gene, MYBPC3, can also lead to LVNC (OMIM number #615396, LVNC10). 9,13 MYBPC3 mutations in HCM lead to an altered primary contractile function.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…9,12 This study confirms our previous results demonstrating that pathogenic variants in another sarcomeric protein gene, MYBPC3, can also lead to LVNC (OMIM number #615396, LVNC10). 9,13 MYBPC3 mutations in HCM lead to an altered primary contractile function.…”
Section: Discussionsupporting
confidence: 90%
“…Like HCM, LVNC is genetically heterogeneous. 9,12 Recently, LVNC was shown to be mainly caused by heterozygous variants in genes encoding sarcomeric Biallelic pathogenic MYBPC3 mutations in neonates MW Wessels et al 15 e Not clear whether these variants are in cis or in trans. f A third variant in MYH7 was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoedemaekers et al. (2010) performed a family screening with both molecular and clinical examinations in 58 patients with LVNC and their 194 family members. This screening revealed that 67% (39/58 patients with LVNC) had a genetic background with these variants.…”
Section: Discussionmentioning
confidence: 99%
“…Mittels genetischer Diagnostik lässt sich mit 35-40 % im Vergleich zu AHF ein deutlich höherer Prozentsatz an Mutationen bei den betroffenen Personen mit LVNC identifizieren [23,25,29]. Dies könnte, trotz der großen Vielfalt an unterschiedlichen Genen, an einem gemeinsamen Entstehungsmechanismus liegen, der auf unterschiedliche Art und Weise während der Entwicklung gestört wird.…”
Section: Nicht-syndromale Strukturelle Herzfehlerunclassified